Monitoring the Changes in Titanium Defect Structure during Titanium Hydrogen Saturation; Russian Journal of Nondestructive Testing; Vol. 55, iss. 12 - Lider A. M. Andrey Markovich; Larionov V. V. Vitaliy Vasilyevich; Xu Shupeng; Laptev R. S. Roman Sergeevich (2019, 2019)
Title screen